230k views
4 votes
Solve by factoring.

m^2+6m+5=0

2 Answers

3 votes

Answer:

-1 and -5

Explanation:

m^2 + 6m + 5 = 0 is factored to: (m + 1)(m + 5) = 0.

The zero product property states that one of the represented parenthesis must equal zero to satisfy the right side of the equation.

(m + 1) = 0

(-1 + 1) = 0

This means that one of the values for m is -1.

(m + 5) = 0

(-5 + 5) = 0

This means that one of the values for m is -5.

Moreover, the value of m by factoring is -1 and -5

User Hanser
by
4.8k points
3 votes

Answer:


  • \sf m=-1,-5

Explanation:


\sf m^2+6m+5=0

Factor, m^2+6m+5

Find, the two numbers that add up to 6 and multiply to 5: 1 and 5

Now, Rewrite the expression:


\sf (m+1)(m+5)


\sf (m+1)(m+5)=0

Now, we will solve the non-linear equation, we can apply the zero product theorem. Each variable factor in the original equation needs to be set to zero.


\sf m+1=0


\sf m+5=0

Now, solve each of the 2 equations:


\sf m+1=0

Subtract 11 from both sides:


  • \sf m=-1


\sf m+5=0

Subtract 5 from both sides:


  • \sf m=-5


\sf m=-1,-5

________________________________________

User Cheila
by
5.4k points